Seasonal variation in the intensity of Gnathostoma larvae in swamp eels (Fluta Alba) sold in a local market in Bangkok - Wichit Rojekittikhun (2018)
The viscera of swamp eels were obtained from a local market in Bangkok twice a month from June 1996 to May 1997. The livers were separated, weighed and counted. Gnathostome larvae were recovered from the livers by the digestion technic, examined, identified, and counted. A total of 12,278 Gnathostoma larvae were obtained from 18,561.1 g (15,264 pieces) of eel livers. The overall average number of larvae/g liver and the overall average number of larvae/liver are 0.91 and 0.94, respectively. The greatest number of larvae/g liver (on average) was in December (high levels of infection during the months of October to December) whereas the lowest was in April (lowest levels of infection during the months of March to April). Thus there was a marked decrease in the average number of larvae/g liver during January to April, which then started to rise in May. This finding suggests that the level of infection abruptly decreases soon after the completion of the rainy season, starts to rise when the rain has come, and reaches its peak when the amount of rainfall is highest. More than 99% of the total gnathostome larvae recovered were identified to be G. spinigerum, and 25.4% of the entire larvae recovered bore variant or abnormal cephalic hooklets. The most common unusual feature was that there were extra rudimentary hooklets above row one, below row four and in between the four rows of hooklets which comprised 21.4%. In addition, the body size and the number of cephalic hooklets of G. spinigerum are also discussed.